2008
DOI: 10.1038/ijo.2008.243
|View full text |Cite
|
Sign up to set email alerts
|

The role of fat topology in the risk of disease

Abstract: Clustering of multiple risk factors such as impaired glucose metabolism, lipid disorders and hypertension has been shown to be the major background of atherosclerotic diseases, and disease entities such as the metabolic syndrome represent a highly atherogenic state. Although these common risks may generally co-exist by accident in one individual, clustering of multiple risk factors in the metabolic syndrome does not occur by accident, and there should be a key player for the syndrome. In 1983, we reported the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 34 publications
8
83
0
1
Order By: Relevance
“…16 Similarly, the results from our study showed that women with preeclampsia had increased plasma concentrations of leptin, PAI-1 and IL-6, but decreased concentrations of adiponectin.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…16 Similarly, the results from our study showed that women with preeclampsia had increased plasma concentrations of leptin, PAI-1 and IL-6, but decreased concentrations of adiponectin.…”
Section: Discussionsupporting
confidence: 77%
“…Although BMI and body weight gain during pregnancy did not differ between preeclamptic women and controls, they are both negatively correlated with plasma adiponectin concentrations in preeclamptic women. As decreased plasma adiponectin concentrations have been reported to be associated with increased visceral fat volume, 16 our results suggest that visceral adipose tissue may accumulate during pregnancy in women with preeclampsia. The mechanism to decrease adiponectin production on accumulated visceral adipose tissue is regarded as TNF-a-dependent pathway.…”
Section: Discussionsupporting
confidence: 68%
“…In fact, the children with the highest waist and waist/height values (450th percentile) were at a greater risk of having a serum 25(OH)D concentration of o70 nmol/l (Table 4). Visceral adipose tissue may have a greater metabolic activity than its subcutaneous counterpart (Matsuzawa, 2008); the sequestration of vitamin D by the former is therefore likely to be Vitamin D status and anthropometric variables E Rodrı´guez-Rodríguez et al greater. More studies are needed to test this hypothesis and to confirm the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 The adipokine repertoire produced by any single adipose repository is probably different depending on the location and many other factors. 50 Certain repositories of adipose tissue (e.g., omental and mesenteric fat in obese human patients) are characterized by the acquisition of an activated macrophage population that secretes proinflammatory cytokines into the venous effluent. 51,52 In obese individuals, these leukocyte-derived cytokines are released in substantial quantities and exert a systemic (endocrine) action.…”
mentioning
confidence: 99%